Engaging Learner Attribute Research in Dialogue with Classroom Practice: Predictors of Success in the Accelerated, Online Classroom - B. Jean Mandernach, Ph.D.; Emily Donnelli, ABD.; Amber Dailey-Hebert, Ph.D. (Journal of Educators Online, 2006)
Research examining student success in online education has focused extensively on internal learner attributes with little emphasis on external, controllable factors that may mediate a student’s ability to perform within the distinctive environment of the virtual classroom. The purpose of this study is to balance student characteristic research with external, direct data from the perspective of online instructors in order to provide a practice-oriented understanding of the unique factors predictive of student success in accelerated, online courses. Experienced online educators were surveyed to identify practical skills, strategies or factors most likely to lead to success for students enrolled in online courses. A content-analysis of open-ended responses revealed 23 relevant factors that clustered into six broad themes. Within these themes, four issues emerge as the most predictive of online learner success: time, technology, initiative, and competence. Discussion examines the practical, deliberate application of this information to facilitate students’ successful completion of online courses.